A Differential Calculus on Superspace and Related Topics - Bulut, Fatma; Celik, Salih (SPRINGER BASEL AG, 2017)
We present a noncommutative differential calculus on the h-superspace via a contraction of the q-superspace, and find a new quantum matrix superalgebra. We also give a new deformation of the super-Heisenberg algebra.
Keywords: h-deformed superspace; Differential calculus; Super Heisenberg Lie algebra; h-deformed quantum supergroup; DEFORMATION; GEOMETRY; Mathematics; Physics